Laposata's laboratory medicine : the diagnosis of disease in clinical laboratory - Laposata, Michael (New York : McGraw-Hill Education, 2019)
"The acclaimed full-color guide to selecting the correct laboratory test and interpreting the results covering ALL of clinical pathology Laboratory Medicine is the most comprehensive, user-friendly, and well-illustrated guide available for learning how to order the correct laboratory test and understand the clinical significance of the results. The book features an easy-to-follow, consistent presentation for each disease discussed. Chapters begin with a brief description of the disorder followed by a discussion that includes tables detailing the laboratory evaluation of specific disorders, diagnosis, baseline tests to exclude diagnostic possibilities, and clinical indications that warrant further screening and special testing. With new, increasingly expensive and complicated tests appearing almost daily, Laboratory Medicine, Third Edition is required reading for medical students, clinical laboratory scientists, and healthcare professionals who want to keep abreast of the latest testing procedures and maximize accuracy and patient safety. Features: 48 clinical laboratory methods presented in easy-to-understand illustrations that include information on the expense and complexity of the assays More than 200 tables and full-color algorithms that encapsulate important information and facilitate understanding Full-color blood-smear micrographs that demonstrate common abnormal morphologies of red blood cells Valuable learning aids in each chapter, including learning objectives, chapter outlines, and a general introduction -- and new to this edition: chapter-ending self-assessment Q&A. Logical systems-based organization that complements most textbooks Extensive table of Clinical Laboratory Reference Values that show the conversions between U.S. and SI units for --
Includes bibliographical references and index.
Keywords: Diagnosis, Laboratory; MEDICAL / Diagnosis